Development and validation of an autoantibody-based blood test for hepatocellular carcinoma - Welberry, Christopher J. (2019)
Hepatocellular carcinoma is the 4th leading cause number of cancer related deaths worldwide. Detection of Hepatocellular carcinoma (HCC) at an early stage is crucial for a positive prognostic outcome, however early detection is hindered by the paucity of early symptoms and interference of underlying liver disease with imaging modalities. Assessment of Alpha-fetoprotein (AFP) as a blood-based screening/diagnostic tool for HCC is still under scrutiny as many HCC tumours do not produce elevated levels and levels can be elevated in other liver disease patients.